2015
DOI: 10.1038/srep13489
|View full text |Cite
|
Sign up to set email alerts
|

Plaque-associated lipids in Alzheimer’s diseased brain tissue visualized by nonlinear microscopy

Abstract: By simultaneous coherent anti-Stokes Raman scattering (CARS) and 2-photon fluorescence microscopy of Thioflavin-S stained Alzheimer´s diseased human brain tissues, we show evidence of lipid deposits co-localizing with fibrillar β-amyloid (Aβ) plaques. Two lipid morphologies can be observed; lamellar structures and coalescing macro-aggregates of sub-micron sizes to ~25 μm. No significant lipid deposits were observed in non-fibrillar, diffuse plaques identified by Aβ immuno-staining. CARS microscopy of unlabeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 57 publications
2
115
0
Order By: Relevance
“…The pathophysiology of AD is due to a combination of factors including systemic inflammation [3], oxidative stress [4], and beta-amyloid plaque formation [5]. Aging and oxidative stress are associated with declines in hippocampal processing of information [68] as demonstrated by the deficits seen in spatial learning, memory formation, and the decline in long term potentiation that is necessary for memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of AD is due to a combination of factors including systemic inflammation [3], oxidative stress [4], and beta-amyloid plaque formation [5]. Aging and oxidative stress are associated with declines in hippocampal processing of information [68] as demonstrated by the deficits seen in spatial learning, memory formation, and the decline in long term potentiation that is necessary for memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, non-destructive identification of amyloids in such tissues becomes possible without introduction of any contaminating agents. This subsequently allows chemical analyses of the identified amyloid structures by vibrational sum-frequency scattering spectroscopy, [70] coherent anti-stokes Raman scattering microscopy, [60,71] and time-of-flight secondary ion mass spectrometry, [72] among other techniques. The fundamental optical properties of amyloids discussed and presented in this paper are essential for continuing efforts with the goal of providing innovative strategies for the study of amyloid fiber structures.…”
Section: Resultsmentioning
confidence: 99%
“…There are growing evidences from in vivo and in vitro studies that lipids are incorporated in the amyloid plaques, which can thus be viewed as lipid-protein co-aggregates [[10], [11], [12], [13], [14], [15], [16], [17], [18], [19]]. Numerous studies have reported that lipid membranes can influence the process of protein aggregation [[20], [21], [22]].…”
Section: Introductionmentioning
confidence: 99%